Saccades and the Müller-Lyer illusion: implications for the two-visual-systems hypothesis - Mackeith, Daisy C.; Knox, Paul C. (British and Irish orthoptic journal, 2012)
Background and aim:  The cortical visual system is divided anatomically into the dorsal and ventral stream. Goodale and Milner in 1992 proposed that this division was functional: the dorsal stream processes ‘vision-for-action’ whereas the ventral stream processes ‘vision-for-perception’. This model of vision is known as the ‘two-visual-systems hypothesis’ (TVSH). Pictorial illusions, such as the Mu¨ ller-Lyer (ML) illusion, have been used by advocates of the TVSH to demonstrate dissociation between visionfor-action and vision-for-perception in healthy subjects. However, this literature is controversial, and not least in experiments investigating the magnitude of the illusion effect on saccades. This review aims to synthesise and critically evaluate evidence from saccade experiments on the effect of the ML illusion, in order to determine whether it provides support for the TVSH. Methods:  Literature searches were performed using the Web of Science, Google Scholar and PubMed. Text books were referred to for additional information. Data were extracted from relevant papers and collated using Microsoft Excel. Statistical analysis was performed using SPSS. Results:  Analysis revealed that saccades are affected by the ML illusion. The magnitude of the illusion effect on saccades is comparable to its effect on perception. Reflexive saccades are affected by the illusion, yet they receive little input from the ventral stream. This is inconsistent with the TVSH as it demonstrates that a dorsally controlled action is affected by a perceptual illusion. Conclusion:  Evidence from experiments on the effect of the ML illusion on saccades provides no general support for the TVSH.